2022
DOI: 10.3390/ijerph192114574
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of CO2 Adsorption-Induced Swelling and Dehydration-Induced Shrinkage on Caprock Sealing Efficiency

Abstract: Carbon dioxide (CO2) may infiltrate into the caprock and displace brine water in the caprock layer. This causes two effects: one is the caprock swelling induced by the CO2 adsorption and the other is the caprock dehydration and shrinkage due to CO2–brine water two-phase flow. The competition of these two effects challenges the caprock sealing efficiency. To study the evolution mechanism of the caprock properties, a numerical model is first proposed to investigate the combined effects of CO2 adsorption-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Illustration showing the dehydration of shale matrix surrounded by a fracture network due to CO 2 infiltration (adapted from the work of Shang et al Copyright: 2022 by the authors. Licensee MDPI, Basel, Switzerland, and distributed under the terms and conditions of the Creative Commons Attribution (CC BY) License).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Illustration showing the dehydration of shale matrix surrounded by a fracture network due to CO 2 infiltration (adapted from the work of Shang et al Copyright: 2022 by the authors. Licensee MDPI, Basel, Switzerland, and distributed under the terms and conditions of the Creative Commons Attribution (CC BY) License).…”
Section: Resultsmentioning
confidence: 99%
“…In his research, Shang et al introduced a multiphysical coupling model to investigate the impact of dehydration and CO 2 adsorption on caprock sealing. 59 He detailed the process wherein CO 2 diffuses from the pre-existing fracture network into the shale matrix, displacing pore water and leading to matrix dehydration shrinkage. Figure 21, extracted from Shang's study, visually represents a shale matrix block surrounded by fractures.…”
Section: Clay Swellingmentioning
confidence: 99%
“…As an effective mitigation strategy for the reduction of CO 2 concentration in the atmosphere, CO 2 geosequestration has received more and more attention (Bachu & Bennion, 2008; Beerling et al, 2020; Huisingh et al, 2015; Isah et al, 2022; Lehmann & Possinger, 2020; Xie et al, 2022). CO 2 injected into the deep ground layer generally migrates in two stages: the first stage is the CO 2 transport within the storage reservoir; the second stage is the CO 2 accumulation beneath caprock (Cai et al, 2021; Heath et al, 2012; Hou et al, 2012; Shang et al, 2022). More and more studies have shown that CO 2 possibly migrates to shallow aquifers and pollutes freshwater resources (Carroll et al, 2014; Keating et al, 2013; Ruggieri & Gherardi, 2020; Smith et al, 2013; Takaya et al, 2017; Wang & Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 migration and interaction in caprocks are complicated (Hu et al, 2022; Zhang et al, 2021). The CO 2 migration in the caprock under the multiphysical‐geochemical interactions may be self‐enhancing or self‐limiting (Gherardi et al, 2007; Hou et al, 2022; Shang et al, 2022; Wang et al, 2015; Wang & Peng, 2014; Yang et al, 2020). Experimental observations showed that the pH value of CO 2 ‐enriched brine decreases and thus leads to calcite dissolution (Huerta et al, 2016; Martín et al, 2022; Niu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation